TENSIONTYPE HEADACHE PADA PERAWAT GILIR DAN NON GILIR DI GEDUNG A RSUPN CIPTO MANGUNKUSUMO DAN FAKTORFAKTOR YANG MEMENGARUHINYA - Muhammad Faisal, Freddy Sitorus, Eva Dewati, Herqutanto (NEURONA, 2012)
INTRODUCTION TENSIONTYPE HEADACHE IS A FREQUENT COMPLAINT EXPERIENCED BY HEALTH WORKERS SUCH AS NURSES IT HAS RESULTED IN DECREASES INWORK PRODUCTIVITY LOSS OF WORKING HOURS AND SIGNIFICANT DISADVANTAGES THE AFFECTING FACTORS ARE DEMOGRAPHY STRES AT WORK AND SLEEP PATTERN ABNORMALITY DUE TO SHIFT WORK THIS STUDY IS CONDUCTED TO DESCRIBE THE PATTERN OF TENSIONTYPE HEADACHE IN SHIFT AND NON SHIFT NURSE AT BUILDING A RSUPN CIPTO MANGUNKUSUMORSCM AND THE AFFECTING FACTORS